ANALISIS YURIDIS P ELAKSANAAN PUTUSAN PENGADILAN AGAMA PEKANBARU TERHADAP PEMBAYARAN NAFKAH ANAK AKIBAT PERCERAIAN - Tanjung, Hardina; Lestari, Rika; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Commensurate with the nature of nature, humans from birth to death to livetogether with another man, or man can not live alone, apart from other human groups.Marriage is an inner and outer bond between a man and a woman who has grown upunder the provisions of the applicable legislation and is eternal and immutable towarddomestic life happy and prosperous. The verdict is the dissolution of marriage that hasbeen fostered by the couple, which is due to several things, such as death, divorce, andthe court's decision. Different partner Al Zuhri and Indrawati, the reason for divorce isbased on the decision of divorce conducted in Pekanbaru religious courts with casenumber, No. 1182 / Pdt.G / 2015 / PA.Pbr with their chronology in the family is not inharmony again because of the people to 3 and environmental factors that lead to quarrelsand disputes continuously so that between husband and wife can not retain the integrityof the family as a reason for divorce Based on the above, the writer wanted to know Howare basic considerations judge in Pekanbaru Religious Court decision against thepayment of a living child of divorce Number: 1182 / Pdt.G / 2015 / PA.Pbr and IsReligion Court decision limiting factor Pekanbaru against payment of a living child ofdivorce and What efforts if Pekanbaru Religious Court decision against the payment of aliving child of divorce is not implementedThis type of research if viewed from the angle of its kind, this research can beclassified in social legal research. Social legal research is the author directly involveddoing research on the location or place of study, the data source used primary legalmaterials, legal materials secondary and tertiary legal materials, techniques of thisresearch with the study interviews and a literature review.From the results of this research and analysis of the author based on theprinciple of legal certainty in mind first, the reasons for the decision in case No. 1182 /Pdt.G / 2015 / PA.Pbr not in accordance with the basic laws and regulations are basedon Article 39 of the Marriage Act No. 1 of 1974, anyone can file a lawsuit on thegrounds: one party committed adultery or an alcoholic, junkie, gamblers, etc. are difficultdisembukhan, one party leaving the other party for two (2) consecutive years without theconsent of others and without a valid reason or because of other things beyond hisability, one party gets a prison sentence of 5 (five) years or severe punishment after themarriage took place.Keywords: Decision, Livelihoods Giving Children, Divorce